Marketing Margin Analysis and Profits of Pork Retailers in Traditional Markets of Gunungsitoli City - Intan Putri Zebua; Edhy Mirwandhono; Tri Hesti Wahyuni; Yunilas .; Hasnudi . (Jurnal Peternakan Integratif, 2018)
Abstract. The demand for pork is related to the supply provided by the market, as well as the ability of farmers and marketing agencies to market livestock products to consumers. Traders plays an important role in determining the sale price of meat and meat offerings. Therefore, research is conducted to find out the marketing process and profit obtained by the final institution. This research was conducted in traditional market of Gunungsitoli City from April to May 2018. The method used in data collection is purposive sampling.In this study, traders who were sampled amounted to 16 people. Analysis includes marketing margins, farmers share, profit pork sharers traders. The results show that there are two marketing channels. Margin on channel two is smaller than channel one. Larger farmers share through two marketing channels is on channel one. Average profit of pork traders for one month per person is Rp.16.699.664,1. Capital factors, working hours, trading experience and the amount of labor affect the profits.